Highly Sensitive Electrical Detection of HIV-1 Virus Based on Scanning Tunneling Microscopy - Lee, Jin-Ho; Kim, Byung-Chan; Oh, Byung-Keun; Choi, Jeong-Woo (AMER SCIENTIFIC PUBLISHERS, 2015)
A highly sensitive immunosensor based on scanning tunneling microscopy (STM) was developed for the first time to detect living material such as HIV-1 virus by gold (Au) nanoparticle and fragmented antibody complex. Fragmented antibodies were pre-immobilized on the Au surface, then HIV-1 virus like particles (HIV-1 VLPs) and Au-nanoparticle and fragmented antibody complexes were applied to develop sandwich assay. The developed surface morphology and the current profile of fabricated immunosensing element were characterized by Raman spectroscopy and investigated with STM. The power spectrum derived from the current profile was found to be related with concentrations of HIV-1 VLPs. Using the electrical detection method based on current mapping profile of STM, living material such as virus, HIV-1 VLPs, was able to be detected successfully. The proposed technique can be a promising method to construct the highly sensitive and efficient sensor for detecting viruses and other living materials.
Keywords: RECOGNITION; PATHOGEN; PROBES; P24